Efficacy and safety of liposome-paclitaxel/liposome-paclitaxel combined with S-1 in 17 advanced gastric cancer patients with poor performance status - Wu, Runhong; Shen, Zhu; Yu, Na; Xu, Jianhao; Yuan, Xuya; Ni, Liwei; Long, Yuming; Tao, Jialong; Zhang, Yusong (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: To evaluate the efficacy and safety of liposome-paclitaxel (L-PTX)/L-PTX plus S-1 in advanced gastric cancer patients with poor performance status (PS). Methods: We performed this retrospective study on 17 advanced gastric cancer patients with poor PS [rated as ≥2 based on the Eastern Cooperative Oncology Group (ECOG) scale] who underwent the following chemotherapy regimen: (I) L-PTX single-agent: L-PTX 60–80 mg/m2 given on days 1 and 8, in a 21-day cycle; (II) timed sequential (TS) regimen: L-PTX 60–80 mg/m2 given on days 1 and 8. S-1, 40–60 mg/m2 twice a day on days 1–14, in a 21-day cycle. Initially, some patients could not tolerate the 2-drug combination chemotherapy regimen, only L-PTX single-agent was given. After the patient’s physical condition was improved, plus S-1 was also given. Results: A total of 17 patients were studied. No complete response (CR) or partial response (PR) were observed in six patients, accounting for 35.29% (6/17). Stable disease (SD) was observed in five patients, accounting for 29.41% (5/17), and progressive disease (PD) in 6, accounting for 35.29% (6/17). The objective response and disease control rates were 35.29% (6/17) and 64.71% (11/17), respectively. The median progression-free survival (PFS) and median overall survival (OS) were 6.50 months [95% confidence interval (CI): 4.81–8.20] and 13.00 months (95% CI: 0.00–33.65), respectively. The most common hematological toxicities were neutropenia and anemia. Conclusions: L-PTX/L-PTX plus S-1 in the treatment of advanced gastric cancer patients with poor PS can prolong the patients’ PFS and OS, and the toxicity is tolerable.